Assessing Exchange Rate Predictability with Statistical and Economic Methods Criterions - Xie, Tingting/T (2019)
This article provides a comprehensive review of the economic models and benchmarks Random work model for out of sample exchange rate forecast. Meanwhile, the assessments of the predictability build upon both economic and statistical methods. By statistical criterion, fundamental economic models provide no more information than the random walk model. However, the fundamental economic models do provide useful information than random walk by the economic standard.